1999
DOI: 10.1073/pnas.96.20.11613
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β differentially regulates calcium wave propagation between primary human fetal astrocytes via pathways involving P2 receptors and gap junction channels

Abstract: In mammalian astrocytes, calcium waves are transmitted between cells via both a gap junction-mediated pathway and an extracellular, P2 receptor-mediated pathway, which link the cells into a syncytium. Calcium waves in astrocytes have also been shown to evoke calcium transients in neurons, and activity in neurons can elicit calcium waves in astrocytes. In this study, we show that in primary human fetal astrocytes, the P2 receptor-mediated and gap junctionmediated pathways are differentially regulated by the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 40 publications
13
140
1
Order By: Relevance
“…In contrast, Cx26 levels were enhanced in response to S. aureus and PGN. Our findings demonstrating the activation-dependent decrease in astrocyte Cx43 expression are in agreement with other reports demonstrating that Cx43 levels are downregulated in astrocytes in response to proinflammatory mediators such as NO and IL-1β (Bolanos and Medina, 1996;Duffy et al, 2000;John et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Cx26 levels were enhanced in response to S. aureus and PGN. Our findings demonstrating the activation-dependent decrease in astrocyte Cx43 expression are in agreement with other reports demonstrating that Cx43 levels are downregulated in astrocytes in response to proinflammatory mediators such as NO and IL-1β (Bolanos and Medina, 1996;Duffy et al, 2000;John et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…In the experimental brain abscess model which has been developed in our laboratory using S. aureus, we have shown that IL-1β and TNF-α play critical roles in CNS pathology . Interestingly, these same proinflammatory cytokines have recently been reported by others to exert dramatic effects on glial homocellular GJC (Chanson et al, 2001;Duffy et al, 2000;Faustmann et al, 2003;John et al, 1999). Based upon this evidence, we propose that proinflammatory mediators released by S. aureus-activated astrocytes in developing brain abscesses may be capable of modulating the nature and extent of GJC, with changes initiated in the proximity of the lesion and consequently extending to affect the surrounding astrocytic syncytial network.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…For instance, exposure of cultured astrocytes to interleukin 1b (IL-1b) downregulates their content of Cx43 at both mRNA and protein levels. 42 This effect is potentiated by another proinflammatory cytokine tumour necrosis factor-a (TNF-a) as well as by b-amyloid. These inhibitory effects are reproduced by co-culturing astrocytes with activated microglia known to release proinflammatory cytokines, indicating that tight interaction occur between glial partners involved in reactive gliosis.…”
Section: Intercellular Communication In Glia and Neuroprotectionmentioning
confidence: 99%
“…Astrocytes function to maintain the homeostatic environment of the CNS and also play an important role in immune regulation, acting as a source of chemokines, cytokines, and effector molecules (Ransom and Sontheimer, 1992;Norenberg, 1997). Coordination of function in astrocyte populations is believed to occur via at least two different mechanisms: an intercellular pathway mediated by gap junctions composed of connexin43 subunits and an extracellular pathway mediated by receptors of the P2 family that respond to nucleotides such as ATP, ADP, UTP, and UDP (Guthrie et al, 1999;John et al, 1999;Scemes et al, 2000). These pathways are thought to provide a mechanism whereby astrocytes are able to sense and respond to changes in the state and activity of neighboring cells and the surrounding CNS microenvironment.…”
Section: Abstract: P2 Receptors; Il-1␤; Human Fetal Astrocytes; Tranmentioning
confidence: 99%